Development of web-based application of medicine management dashboard for pharmacists in primary health care using a user-centered design: evidence from Indonesia - Faradiba, Faradiba; Satibi, Satibi; Lazuardi, Lutfan; Ivanawati, Anselma (Faculty of Pharmacy, Universitas Pancasila, 2024)
Although the minimum standard of pharmaceutical services at the primary health centres (PHCs) has been determined, the quality of drug management at PHCs is not optimal. There is no information system in PHC to help pharmacists monitor drug management performance. This study aims to describe the systematic development of such an application. A descriptive study with a case study approach was conducted, consisting of three stages: user needs analysis, model and prototype development, and prototype evaluation. The first stage in the user-centred design method is through focus group discussion and observation. There were 13 institutions involved in the needs analysis and 9 institutions in the evaluation stage by purposive sampling. The institutions are health centres and offices in Yogyakarta from September 2021 to April 2022. Data were analysed using descriptive qualitative and quantitative methods. The research resulted in a prototype web application, PharmD, which functions as a drug management performance dashboard for pharmacists at PHCs.